A Better Trigger: Indices for Insurance. Issue 4 (28th February 2018) - Teh, Tse‐Ling; Woolnough, Christopher
Abstract: Index triggers have enabled the extension of insurance to a wide range of risks, by providing a simple mechanism to determine payment. However, the resulting coverage generates basis risk, the variability over time in the level of insurance payouts relative to the level of losses. We analyze basis risk to rank binary and multivalue indices for any risk‐averse individual. Our ranking provides methods to select an index that is optimal for a heterogeneous group and illustrates that higher correlation between loss and index, does not necessarily equate to a better index.